Nutritional contribution of pollen from species pollinated by bees (Apis mellifera L.) in the Araucanía Region of Chile - Araneda, Ximena; Caniullan, Roger; Catalán, Carol; Martínez, María; Morales, Daniza; Rodríguez, Mario (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The present paper aims to determine the nutritional contribution of pollen from four cultivated species (Malus domestica Borkh., Eucalyptus globulus Labill., Brassica napus L. ssp. oleifera and Vaccinium corymbosum L.) pollinated by bees (Apis mellifera L.) in Southern Chile. The pollen was collected in helicoidal pollen traps installed in hives in farms located in different parts of the Region, and was subsequently analysed at the Bromatology Laboratory. The results obtained matched the values described in the literature, with ranges of phosphorus between 0.59 and 0.80%, crude protein between 33.27 and 39.04%, ethereal extract between 1.83 and 7.72%, carbohydrates between 19.62 and 39.18% and total polyphenols contents ranging between 2,643.69 and 4,773.28 mg 100 g-1. Thus the species evaluated may be considered sources rich in proteins, carbohydrates and polyphenols; however it is important to determine the composition and concentration of amino acids, sugars and fatty acids present in the pollens.